2019
DOI: 10.2478/amb-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Gastrointestinal Cancer Risk: A Review

Abstract: Introduction: Western lifestyle characterized by increased consumption of red meat, fat, processed food, smoking, alcohol drinking, lower consumption of vegetables and physical inactivity has been associated with a higher gastrointestinal cancer risk. Digestive system cancers are diagnosed at late stages when they show poor response to treatment and are associated with a high mortality rate. Colorectal, gastric, esophageal and pancreatic cancers are among the most common cancers worldwide. Studies show that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 125 publications
(254 reference statements)
0
4
0
Order By: Relevance
“…Regular physical activity may lower cancer risk. Several studies have demonstrated that avoiding a sedentary lifestyle and participating in physical activities is helpful for reducing the risk of digestive system cancers ( Tayyem et al, 2013 ; Tajabadi et al, 2019 ). In the current study, most participants with GC and PC (70.9% and 73.0%, respectively) were considered minimally active (physical activity level between 600~3,000 MET-min/week) and were significantly less active than the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regular physical activity may lower cancer risk. Several studies have demonstrated that avoiding a sedentary lifestyle and participating in physical activities is helpful for reducing the risk of digestive system cancers ( Tayyem et al, 2013 ; Tajabadi et al, 2019 ). In the current study, most participants with GC and PC (70.9% and 73.0%, respectively) were considered minimally active (physical activity level between 600~3,000 MET-min/week) and were significantly less active than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhang et al (2009) showed that participants with PC were less physically active than controls. Tajabadi et al (2019) stated that the type and intensity of physical activity associated with a protective effect against gastro-intestinal cancer is unknown. Furthermore, the exact underlying mechanisms linking physical activity to digestive system cancers are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations